PROMOSI KESENIAN TARI BANGILUN DUSUN JATI BERBASIS WEBSITE - Fajar Hidayanto (Asian Journal of Innovation and Entrepreneurship, 2015)
Every region in Indonesia is rich in cultural diversity, one of them is Bangilun dance of Dusun Jati, Desa Gerbosari, Samigaluh, Kulon Progo, Yogyakarta. Villagers triedto keep preserved. Although they had showed up the dance in some big  events inYogyakarta and Jakarta, public still do not know about Bangilun dance because people ofDusun Jati do not know how to promote well. Therefore, the authors intend to helpthem to promote Bangilun dance by by providing training and make a website. As aresult, citizens are able to promote well and get more attention from visitors.